1987
DOI: 10.1002/ssu.2980030402
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomas of the jaw

Abstract: A retrospective analysis is made of 61 patients with clinical and histological diagnosis of pure sarcomas of the jaw treated between 1950 and 1984. Surgery was the treatment of choice in 41 cases. Biopsy or palliative treatment were undertaken in the remaining patients. Twenty-four cases relapsed before 12 months, and 12 relapsed before 3 years. Twenty-four died before 12 months, nine before 2 years, and three after 2 years. At present there is no evidence of disease in eight patients: three out of 25 fibrosar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The present study did not find this type of distribution and, in fact, found a progressive decrease of cases occurring as age increased. When the diagnoses were compared in the current study, a 51.1% predominance of osteosarcomas was found, which is high compared with 24.6% reported by Yoel et al 9 or 28% reported by Yamaguchi et al…”
Section: Discussionmentioning
confidence: 36%
See 1 more Smart Citation
“…The present study did not find this type of distribution and, in fact, found a progressive decrease of cases occurring as age increased. When the diagnoses were compared in the current study, a 51.1% predominance of osteosarcomas was found, which is high compared with 24.6% reported by Yoel et al 9 or 28% reported by Yamaguchi et al…”
Section: Discussionmentioning
confidence: 36%
“…This value is similar to that described by Brockstein. 8 In turn, Yoel 9 and co-workers report similar data, citing greater predominance of JS in the second, third, fourth, and fifth decades of life. The literature describes a bimodal age group distribution for osteosarcomas, in which the majority of patients are between 10 and 20 years old, with a secondary group over 50 years old.…”
Section: Discussionmentioning
confidence: 50%